Analysis of Potential Hazards and Risks of Work Accidents by Using the HIRARC Method On Earthwork and Geosynthetics - Kuncaravita, Sekar Ayu; Apriliani, Rizki Astri; Lawdy D.V, Muhammad; Indri Y, Dayat (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2025)
The world of construction always has potential hazards and risks that always endanger the safety and health of workers. The occurrence of work accidents is an event that is always unexpected and can cause losses, both for the construction company and the workers. This study aims to determine the potential hazards in an effort to reduce work accidents in the Banjarsari- Dukuh Tengah road improvement project in Sidoarjo Regency. The method used in this research is hazard identification risk assessment and risk control (HIRARC). The results showed that in the construction of the Banjarsari- Dukuh Tengah road improvement project in Sidoarjo Regency, especially in earthworks and geosynthetics, there were 10 jobs in the Banjarsari- Dukuh Tengah road improvement project in Sidoarjo Regency showing that the potential hazards were 2 activities classified as having a "low risk," 3 activities with a "medium risk," and 5 other activities with a "high" risk. To overcome these problems, suggestions for improvement are given so that workers carry out work activities in accordance with standard operating procedures (SOPs) and wear personal protective equipment (PPE).